Assessment of Trihalomethane Formation in Chlorinated Raw Waters with Differential UV Spectroscopy Approach. (2nd December 2013) - Özdemir, Kadir; Toröz, İsmail and Uyak, Vedat
Abstract : In this study, the changes in UV absorbance of water samples were characterized using defined differential UV spectroscopy (DUV), a novel spectroscopic technique. Chlorination experiments were conducted with water samples from Terkos Lake (TL) and Büyükçekmece Lake (BL) (Istanbul, Turkey). The maximum loss of UV absorbance for chlorinated TL and BL raw water samples was observed at a wavelength of 272 nm. Interestingly, differential absorbance at 272 nm (Δ UV 272 ) was shown to be a good indicator of UV absorbing chromophores and the formation of trihalomethanes (THMs) resulting from chlorination. Furthermore, differential spectra of chlorinated TL waters were similar for given chlorination conditions, peaking at 272 nm. The correlations between THMs and Δ UV 272 were quantified by linear equations with R 2 values >0.96. The concentration of THMs formed when natural organic matter is chlorinated increases with increasing time and pH levels. Among all THMs, CHCl3 was the dominant species forming as a result of the chlorination of TL and BL raw water samples. The highest chloroform (CHCl3 ), dichlorobromomethane (CHCl2 Br), and dibromochloromethane (CHBr2 Cl) concentration were released per unit loss of absorbance at 272 nm at pH 9 with a maximum reaction time of 168 hours and Cl2 /dissolved organic carbon ratio of 3.2.